Determinants of microblog music review credibility and its influence on electronic word of mouth (eWOM) adoption. - Mazibuko, Mdumiso (Vaal University of Technology, 2019)
While more than half of the South African adult population are active microbloggers, the most common topics that are discussed include current affairs, sports and music entertainment. Nonetheless, there exists intrinsic fear about the credibility of digital content, which stems from the fact that there are limited standards for quality control in the microglogging sphere. Consequently, this apprehension exacerbates potential problems pertaining to ascertaining the reliability of electronic word of mouth (eWOM) communication. In this vein, this study seeks to investigate the salience of selected determinants on consumers’ perceptions about the credibility of microblog music reviews and future eWOM adoption. The sample comprised 485 self-reporting microbloggers residing in the southern Gauteng region of South Africa. The study applied a quantitative approach, whereas cross-sectional data were collected only once from the sample using a paper and pencil based self-administered questionnaire in 2018. Moreover, a positivist philosophy was followed, whereas hypotheses were framed from the credibility heuristics theory, posited as the underlying cues that aid consumers in the online credibility verification process. The formal protocol for research ethics were followed upon collecting empirical data, whereas the multi-item survey questionnaire was tested for reliability and validity. The hypotheses testing comprised an estimation of two regression models. From the findings obtained, it is evident that source credibility, information quality, homophily and prior beliefs confirmation are the four heuristics that pose a significant effect on the evaluation of microblog music reviews by consumers, yielding approximately 43.3 percent explanatory power on the overall credibility of microblog music reviews. Moreover, the second regression model proved the positive effect of microblog music review credibility on eWOM adoption, whereas the independent variable explains 30.7 percent of the variance in eWOM adoption. These findings point to the significance in applying the heuristics in evaluating microblog music reviews created by South African consumers. As such, the findings could assist both microblog administrators and marketing communication practitioners to better design the platforms to facilitate reader credibility evaluations about various products.
M. Tech. (Department of Marketing, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Credibility; Heuristics; Music reviews; Microblogs, South Africa; Dissertations, Academic -- South Africa; Microblogs -- Social aspects -- South Africa; Social networks; Truthfulness and falsehood; Music -- Social aspects